Hubungan Bobot Telur dan Indeks Telur dengan Bobot Tetas Itik Dabung di Kabupaten Bangkalan - Mahardika Setya Okatama; Sucik Maylinda; V.M Ani Nurgiartiningsih (Jurusan Produksi Ternak, Fakultas Peternakan, Universitas Brawijaya, 2018)
ABSTRACKBangkalan Regency has a potensial local Dabung duck. A study was conducted on the duck eggs, including egg weight, egg index and hatching weight. This study aims to determine the relationship between egg weight and egg index with hatching weight. The research material was 150 eggs of Dabung duck. The origin of eggs was from the parent duck with the age ±7-9 months and the age of eggs was 1-5 days. Research methods the experiment with how to incubate Dabung duck eggs in a simple to use machine incubate. Dabung duck analysis result showed average egg weight 63,65g/egg, egg index 76,50% and hatching weight 43,03g/tail. Positive correlation relationship between egg weight with hatching weight and give a real influence (P<0.05), while the egg index with hatching weight shows a positive correlation relationship and shows real influence (P<0.05). The results of the regression analysis (A) shows Dabung duck egg weight with hatching weight Y=-1.809+0.704X. Results of a regression analysis (A) shows the egg index with hatching weights Y=10.619+0.424X. Regression coefficient of the egg weight and the egg index are positive. Results of the regression analysis (B) of egg weight and eggs index with hatching weight Y=-16.312+0.694X1+0.198X2. Regression coefficients are positive. Result showed that Dabung duck has average egg weight 63.65 g/egg, egg index 76.50% and hatching weight 43.03g/tail. Correlation between egg weight and egg index with hatching weight was significant (P<0,05). Regression (A) and (B) in Dabung duck indicate the of the relationship of egg weight and egg index to hatching weight is positive. Keywords :